Nattokinase as a functional food ingredient: therapeutic applications and mechanisms in age-related diseases - Hao Wu; Qian Zhang; Hao Suo; Feng Xu; Wanxu Huang; Dan Ohtan Wang (Food Science and Human Wellness)
Consumption of natto, a traditional eastern Asian food made of fermented soybeans by Bacillus subtilis, has long been linked to healthy aging and longer human lifespan. As the key thrombolytic ingredient of natto, the serine protease nattokinase (NK) has been developed into a widely-used dietary supplement. NK has shown excellent anti-thrombus, thrombolytic, and anti-inflammation activities that potentially delay aging and provide therapeutic effects on aging-related diseases. In this review, we critically overview the experimental and clinical evidence in the past 20 years that support the beneficial function of NK in the prevention and treatment of aging-related diseases, including cardiovascular diseases, Alzheimer’s disease, other abnormalities and cancer. We focus on the underlying molecular mechanisms and recent advances in application methods that are aimed at further development of NK for healthier aging of modern society. The challenges and unsolved issues in this area are also discussed.